Besov Spaces for Isometric G-Actions - Schulz-Baldes, Hermann; Stoiber, Tom (Springer, 2022)
Classical Sobolev, Besov and Triebel-Lizorkin spaces measure smoothness and integrability properties of functions on Rn simultaneously. From several points of view, the Besov spaces are particularly well-behaved [1] which is why they appear naturally in numerous contexts. Relevant for the present context is Peller’s characterization of traceclass properties of Hankel operators by Besov regularity of their symbols [2]. Furthermore, it is remarkable that in trace theorems there is no loss of Besov regularity (other than for Sobolev spaces) [1].
CRIS-Team Scopus Importer:2024-12-16